PEMANFAATAN MEDIA PEMBELAJARAN MATEMATIKA DIGITAL BERBASIS EDUGAME WORDWALL TINGKAT SEKOLAH DASAR DI DESA SIDOREJO - Donna Avianty; Nopem K. Sumitro; Devi Putri Yuliantika; Diah Apriliani Rahmatun; Vita Noviyanti Mulyaningsih (JPM PAMBUDI, 2023)
One of the aims of this Potential-Based Community Service is to increase enthusiasm for learning mathematics and introduce fun mathematics learning for children in Sidorejo Village. Because all this time learning mathematics seems very scary and less fun if it is studied with the wrong method. This problem becomes a separate focus point for each element of education. The implementation method in this activity was carried out in Sidorejo Village, Jabung District, Malang Regency by applying face-to-face edugame wordwall-based digital mathematics learning with elementary school level children. After implementing this activity, it can be concluded that by utilizing digital mathematics learning media with wordwall software, it can improve students' abilities and enthusiasm in learning mathematics.